Towards a normative model for managing container shipping supply chains - Lam, Jasmine Siu Lee (2013)
This paper aims to propose a normative model and derive hypotheses for managing container shipping supply chains, with the goal to better synchronise the processes and the partners involved in practice. Formulation of the research approach follows a scientific and systematic research design, particularly conceptual theory building. A more integrated supply chain approach is useful in exploring ways to increase the competitiveness of container shipping. Total cost concept, economies of scope, demand complementarity, market power theories and obstacles to integration are applicable in explaining the evolutions in container shipping in the supply chain context. The study leads to better conceptualisation and contributes to the scant literature in an important and emerging research topic. It amalgamates, enhances and simulates multidisciplinary supply chain research. This paper contributes by developing an original normative model for managing container shipping supply chains which can serve practical and research purposes in planning, execution, monitoring and benchmarking.